The risk factors and maternal adverse outcomes of stillbirth - Simsek, Deniz; Demirci, Ahmet; Dinçgez Çakmak, Burcu (Journal of Surgery and Medicine, 2021)
Background/Aim: Stillbirth is a devastating complication of the pregnancy. Contemporary studies have exposed several reasons; however, most of the cases are still unexplained. Stillbirth delivery could cause various maternal complications. We aimed to evaluate the maternal complications and reveal the risk factors for stillbirth. Methods: A case-control study was performed at a high-volume university-affiliated research and training hospital between June 2016 and June 2020. The study population was divided into two groups as women who delivered stillbirth (study group) and live birth (control group). Patients’ characteristics, birth weight and gender of the newborn, hospital stay, delivery type, concomitant diseases in pregnancy such as preeclampsia, gestational diabetes mellitus, fetal anomaly, preterm premature rupture of the membranes and complications such as uterine atony, abruptio placenta, postpartum hemorrhage, disseminated intravascular coagulation, and uterine rupture were evaluated from the medical records and compared between groups. Results: A total of 46019 births occurred during the study period. The number of women who delivered stillbirth was 520 with a rate of 11.2 per 1000 births. The control group included 6521 patients. Comparison of the groups revealed that women delivering stillbirth were older (P<0.001), had longer hospital stay (P<0.001), lower newborn birth weight (P<0.001), and more babies with congenital anomalies (P<0.001) than the control group. The women in stillbirth group experienced more preterm premature rupture of the membranes (P<0.001), preeclampsia (P<0.001), gestational diabetes mellitus (P<0.001), abruptio placenta (P<0.001), postpartum hemorrhage (P<0.001), and disseminated intravascular coagulation (P<0.001). The rates of severe obstetric and postpartum complications were 14.2% and 12.1%, respectively. Multivariate logistic regression analysis revealed that fetal anomaly (OR 3.170; 95% CI 1.592-6.315, P<0.001), gestational diabetes mellitus (OR 15.203; 95% CI 8.368-27.621, P<0.001) and abruptio placenta (OR 18.221; 95% CI 9.121-36.402, P<0.001) increased the risk of stillbirth. Conclusion: Stillbirth delivery could lead to severe maternal complications that can threaten maternal vitality. Close delivery follow-up is essential, especially during the early postpartum period. Care should be taken for postpartum complications such as disseminated intravascular coagulation and postpartum hemorrhage. Furthermore, patients should be examined carefully for abruptio placenta. Stillbirth deliveries should be carried out in fully equipped hospitals.